Fostering School Quality and Parental Participation: The Strategic Impact of Women’s Transformational Leadership and Innovation - Dwi Yani; Loso Judijanto; Sarlota Singerin; Narendra Jumadil Haikal Ramadhan; Aisyah Ali; Solicha Solicha (Jurnal Pendidikan Progresif, 2026)
This study aims to evaluate the impact of women’s transformational leadership within leadership innovation programs on school quality and parental participation. While transformational leadership has been widely studied, research on the specific contributions of female leaders in educational contexts remains limited. This study addresses that gap by examining how women’s leadership practices foster inclusive school cultures, enhance teacher motivation, and build stronger family–school partnerships. A quantitative, cross-sectional, correlational design was utilized. Data were collected from 100 teachers in Malang City, Indonesia, led by female principals, using a structured questionnaire on transformational leadership, school quality, and parental participation. The data were analyzed with Structural Equation Modeling (SEM) using SmartPLS to test measurement reliability and examine relationships among variables. The results indicate that women’s transformational leadership significantly influences the implementation of leadership innovation programs, thereby strengthening both parental participation and school quality. Leadership innovation programs mediated the relationship, showing strong indirect effects on educational outcomes. Direct effects were also confirmed: women leaders’ practices of empathy, collaboration, and participatory communication were positively associated with teacher engagement, parental involvement, and improved school quality. These findings highlight the unique relational strengths of female transformational leadership in fostering inclusive and effective educational environments. Conclusion: Empowering women leaders through leadership innovation programs is vital to enhancing school effectiveness. Women’s transformational leadership not only drives innovative practices but also reinforces trust-based collaboration among teachers, parents, and administrators. The implications suggest that policies should prioritize inclusive leadership development for women to ensure sustainable improvements in parental participation and school quality. This research contributes to a deeper understanding of the strategic role of female leadership in shaping resilient and high-performing schools. Keywords: leadership innovation programs, women’s transformational leadership, school quality, parental participation.